Prevention of rhesus immunization in the presence of a potential sensitizing factor - Nasirova Durdonakhan Yusupjonovna.; Saidjalilova Dilnoza Djavdatovna (Zien Journals, 2023)
In this article, prevention of rhesus immunization in the presence of a potential sensitizing factor, the development of hemolytic disease of fetuses and infants, and disorders of fetal erythrocytes are described in detail
Keywords: potential sensitizing factor; prevention of rhesus immunization; hemolytic disease